Clustering and regional growth in the housing market: Evidence from Indonesia - Ariyanto Adhi Nugroho; Muhammad Yusuf Indra Purnama; Laela Rizki Fauzia (Jurnal Keuangan dan Perbankan, 2020)
The housing market is one of the monetary policy instruments in macro-prudential terms. The overall policy adopted through the Loan-to-Value ratio does not accommodate different regional characteristics. Location and area characteristics are important factors that influence the development of housing property prices. This study uses panel data regression analysis, with objects of 15 cities in Indonesia during 2007-2017. The results of the analysis provide a proof that the building rent, population density, construction costs, Gross Regional Domestic Product, unemployment rate, and minimum income, affect housing prices differently in each growth category, while the LTV ratio and inflation do not have a significant effect onto house prices. The regional economic growth is used to form regional clustering based on the speed of house price growth so that monetary policy in the housing sector achieves the target.JEL Classification: E52, O18, R58 How to Cite:Nugroho, A. A., Purnama, M. Y. I., Fauzia, L. R. (2020). Clustering and regional growth in the housing market: Evidence from Indonesia. Jurnal Keuangan dan Perbankan, 24(1), 83-94.DOI: https://doi.org/10.26905/jkdp.v24i1.3565